Application Review of Network Attack Detection Based on Deep Learning - Liu, Yixuan; Yu, Jiaohang (Transactions on Computer Science and Intelligent Systems Research, 2025)
With the rapid development of the Internet, network attacks (NA) have become increasingly diverse and sophisticated. Traditional detection methods relying on rules systems and statistical analysis now face significant challenges, including strong dependency on feature engineering and limited generalization ability. The effectiveness of detection systems is not only limited, but the difficulty of addressing new threats is also increased. Deep learning has been recognized as a novel solution for NA detection due to its powerful nonlinear feature extraction capabilities and end-to-end learning paradigm. A concise overview of deep learning fundamentals is first provided. Subsequently, the paper proceeds with a systematic review of prevailing deep learning approaches for NA detection, followed by an analysis of their current limitations and challenges in NA. Finally, promising future research directions are proposed to address the aforementioned limitations and challenges.